Development of Digital Economy Regulatory Environment in Supply Chain Operations - Ukolov Vladimir; Cherkasov Vitaly (International Journal of Supply Chain Management, 2019)
The article studies the insufficiently studied problem of digital economy regulatory environment development in supply chain operations, the interaction of the real and virtual sectors. The authors set the goal to analyze various aspects of this problem, to justify the supply chain strategy and the mechanisms for its solution. The article shows that digitalization, spreading in cyberspace and not supported by legal norms, represents a real threat to the development of fair competition and state sovereignty preservation. It is proved that digitalization causes the need to reformat the legal system, its basic foundations, content and application mechanisms. However, this reformatting is constrained by legal system differences used in the global community. The study made it possible to argue the need to develop model legislation on the key issues of modernity and the systemic use of digital sovereignty by states. The article used the methods of situational, structural and dynamic analysis, which contributed to the study of existing ideas about the interaction of enterprises of real and virtual sector of the economy, including government regulation of emerging problems. A systematic approach was used during the evaluation of digital economy regulatory environment. Research has revealed the systemic nature of various factor combination influence influencing the development of digital economy regulatory environment. Practical significance of study materials. The materials of the article are of practical value for public administration, government institutions, the public sector and business structures. The obtained research results are used in practice during digital economy regulatory environment development, the interaction of the real and virtual sectors. Their use contributes to the change of legal norms, the creation of conditions conducive to fair competition of relation subjects in the economic sphere and ensuring the security of state digitization.